Disutopian Manifestations in the Algerian Novel: A Case Study "Watan Men Zojaj, A Fragile Homeland" - Alkrenawi, Fareda Jmea'an (Journal of Arabic Language Sciences and Literature, 2023)
Literature is considered a medium by which a society could be mirrored. It is a barometer of the daily experiences we go through; thus, reflecting both the volatility and the evolvement taking place within a given community. Because the events ultimately take place in the realm of space and place, the Arabic city has been largely portrayed in the literary work. The imagery of the Arabic city delineated the good, the bad and the ugly changes within the society. When the events tracked are for the better, it is then that the Arabic city would be referred to as Utopia. Conversely, when the the events described are those of pain, suffering, extreme poverty and indiscriminate violence, it is then that the Arabic city is portrayed as dystopia, an incompatible and unsuited place for human thriving.Terror and violence have permeated many of the Arab countries. This phenomenon has been tracked and portrayed in much of the literary work. It was delineated in quite a few creative novels. These novels stand out as a witness of the phenomenon, thus, creating disutopean literature. It is a literary space which portrays the miserable and unbearable reality. In this particular space, death hovers everywhere. The present reality becomes evidence of the obscure future; furthermore, the nostalgic memories become a prerequisite in the hearts of the individuals. Therefore, the disutopia, the dysfunctional city , in the Arabic literature reflects the daily lives of the individuals and their happier past: this is the ultimate expression of suffering and misery.In our study, we examine the portrayal of violence and dysutopia in the Arabic literature, specifically, in the novel, “Watan men zojaj”, A Fragile Homeland, by Yasmeena Saleh, in which she addressed the critical era that Algeria had witnessed. It is a ten years period, at which death, destruction, assassination and hijacking has created intense national crisis. Thus, Algeria evolves into a guerrilla war zone in which the citizens could not live in security. We found in our study, that the author was able to portray the disutupian reality in Algeria and were able to follow its ripple effects on time, place and the individuals.
Keywords: Arabic novel; Disutopian literature; civil war in Algeria; violence